Pseudo-progression with osimertinib after definitive chemoradiation in unresectable epidermal growth factor receptor mutation positive of stage III non-small cell lung cancer: A case report - Ren, Fei; Wang, Yao; Gao, Yongsheng; Meng, Xiangjiao (Frontiers in Oncology, 2022)
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) have been widely used in the treatment of locally advanced non-small cell lung cancer (NSCLC). The phenomenon of pseudoprogression in targeted therapy in EGFR-mutation NSCLC patients is rare. Here we reported a EGFR-mutation positive lung adenocarcinoma patient, who was admitted to hospital for cough and chest distress accompanied by shortness of breath. He underwent four cycles of chemotherapy with pemetrexed combined with carboplatin and concurrent radiotherapy in the third and fourth cycle. Then, he was treated by osimertinib maintenance therapy. After 11.5 months of osimertinib treatment, he was assessed to progressive disease by computed tomography. He underwent a fiber bronchoscopy, and the biopsy pathology showed extensive necrosis without tumor cells. Until now, the patient has continued on osimertinib for 7 months without relapse or metastasis. As far as we know, we are the first to report pseudoprogression in osimertinib maintenance after definitive chemoradiation. This study reminds the clinicians to distinguish pseudoprogression from osimertinib-induced progression and avoid abandoning effective treatments.